Essays on agricultural commodity processing - LI, Bin (Institutional Knowledge at Singapore Management University, 2020)
This dissertation investigates two important issues in agricultural commodity processing: (i) biomass commercialization; that is, converting organic waste into a saleable product, from economic and environmental perspectives, and (ii) optimal procurement portfolio design using multiple suppliers and spot market, and the impact of by-product introduction on this optimal portfolio. The first chapter examines the economic implications of biomass commercialization from the perspective of an agri-processor that uses a commodity input to produce both a commodity output and biomass. We characterize the value of biomass commercialization and perform sensitivity analysis to investigate how spot price uncertainty (input and output spot price variabilities and the correlation between the two spot prices) affects this value. We find that commercializing biomass makes the profits less sensitive to changes in spot price uncertainty. Using a model calibration in the context of palm industry, we show that the value of biomass (palm kernel shell) commercialization can be as high as 26.54% of the processor (palm oil mill)’s profits. The second chapter examines the environmental implications of biomass commercialization. To this end, we characterize the expected carbon emissions considering the profit-maximizing operational decisions using the economic model of the first chapter. In comparison with the common perception in practice, which fails to consider the changes in operational decisions after commercialization, we identify two types of misconceptions (and characterize conditions under which they appear). In particular, the processor would mistakenly think that commercializing its biomass is environmentally beneficial when it is not, and vice versa. Using a model calibration, we show that the former misconception is likely to be observed in the palm industry. we perform sensitivity analyses to investigate how a higher biomass price or demand (which is always economically superior) affects the environmental assessment and characterize conditions under which these changes are environmentally superior or inferior. Based on our results, we put forward important practical implications that are of relevance to both agri-processors and policy makers. The third chapter studies the procurement portfolio design of an agri-processor that sources a commodity input from two suppliers that use quantity flexibility contracts---characterized by reservation cost and exercise cost---to produce and sell a commodity output under input and output spot price uncertainties. We characterize the optimal procurement portfolio that is composed of three strategies---single sourcing from the supplier with lower reservation price, and single sourcing from the supplier with lower exercise price, and dual sourcing. We investigate how the spot price correlation shapes the optimal procurement strategy and the value of using suppliers. We then study the impact of introducing a non-commodity by-product on the optimal procurement portfolio. Based on our results, we put forward important managerial implications about the procurement strategy and by-product management in agricultural processing industries.